Odpowiedź :
Odpowiedź:
a)9x+2
b)-7a+2b-5c +54
c)-2x+1y-11
d)3x -2y+5 -9x-4y+7=-6x-6y+12
2.
9-1+1 -3a -9b+6c= 9-4,5 +1,5=6
Odpowiedź:
1.
A. (8 + 4x - 2y) + (5x + 2y -6) = 8 + 4x - 2y + 5x + 2y -6 = 8 + 4x + 5x - 6 = 2 + 9x
B.(-3a + 2b -5c) - (4a – 50) + 4 = -3a + 2b -5c - 4a – 50 + 4 = -7a + 2b - 5c + 50 + 4 = -7a + 2b - 5c + 54
C.4(x – 2y -5)-3(2x - 3y + 2) = 4x - 8y - 20 - 6x + 9y - 6 = -2x + y - 26
D.(15x - 10y + 25): 5 - (3x + 12y-21): 3 = 75x - 50y + 125 - (3x + 252y) : 3 = 75x - 50y + 125 - 3x + 252y/3 = 75x - 50y + 125 - 3x (x + 84y)/3 = 75x - 50y + 125 - (x + 84y) = 75x - 50y + 125 - x - 84y = 75x - 134y + 125
2. przepraszam nie rozumiem go :(
Szczegółowe wyjaśnienie:
Mam nadzieje że pomogłam liczę na naj :)